Workplace Violence Against Nurses in Psychiatric Hospital Settings: Perspectives from Saudi Arabia - Wafa Basfr; Ahlam Hamdan; Samia Al-Habib (Sultan Qaboos University Medical Journal, 2019)
Objectives: Workplace violence (WPV) has become a world-wide concern. This study aimed to measure the prevalence of WPV among nurses working in psychiatric hospitals in Saudi Arabia. Methods: This cross-sectional study was conducted at three psychiatric hospitals in Saudi Arabia between March and May 2017. Participants completed a self-reported questionnaire which was used to measure the prevalence and explore the associated factors of WPV. A multivariate logistic regression analysis was also performed. Results: A total of 310 nurses (response rate: 62%) were included in this study. The prevalence of WPV against nurses was 90.3%, of which 57.7% had been exposed to both physical and verbal abuse. More nurses were exposed to WPV during the morning shift than the evening shift (58.4% versus 42.3%). Violent behaviour was exhibited mostly by the patients themselves (81.3%). Over half of the nurses (57.4%) required medical intervention in such cases. The majority of nurses felt either stressed (64.2%) or anxious (53.5%) and 34.2% felt depressed after the incident. Multivariate logistic regression analysis revealed that time of violence, source of violence, patient dissatisfaction with medical care and lack of organisational support for nurses were significantly associated with the occurrence of WPV in psychiatric units. Conclusion: WPV has reached an alarming rate among nurses in psychiatric hospitals in Saudi Arabia. It is crucial to invest in the prevention of WPV by constant training of workers and a mutual policy with the police and the civic prosecutor in Saudi Arabia on how to respond to violent psychiatric patients.